Identifikasi Lokasi Ziarah dan Estimasi Volume Limbah Bunga di Lokasi Ziarah Kota Banjarmasin - Sharfina Puteri Amima; Muhammad Rahmattullah; Dwi Atmono; Taufiqurrahman Taufiqurrahman (Jurnal Zona, 2026)
The practice of pilgrimage in Banjarmasin City, rooted in spiritual and cultural beliefs, raises significant environmental issues related to flower waste. This study aims to identify key pilgrimage sites and estimate the volume of flower waste generated at three iconic sites: the Tomb of Guru Zuhdi, the Dome of Habib Basirih, and the Tomb of Sultan Suriansyah. The study used mixed methods, combining qualitative descriptive analysis through in-depth interviews and observations, and quantitative analysis through direct waste weighing over seven consecutive days. The results indicate that the flower-sprinkling ritual is a deeply rooted tradition but also has significant environmental consequences. The quantitative analysis demonstrates that the three pilgrimage sites collectively generate substantial volumes of flower waste, with a total estimated at over 5.2 tons per year. This data highlights that the issue of flower waste is not merely an aesthetic issue but also an environmental challenge that requires special attention, especially when volumes increase dramatically during the pilgrimage season. This study identifies the gap between cultural practices and effective environmental management, while also highlighting the economic potential of flower waste as a compostable resource. These findings provide a data-based foundation for formulating sustainable waste management strategies that can be integrated with the cultural and religious values of the community. This research contributes to the literature by providing specific quantitative data, previously scarce in the context of pilgrimages in Indonesia